An optimized sustainable medium for the direct lactic acid fermentation of sago ( Metroxylon sagu rottb.) starch by Enterococcus faecium DMF78 - Kobayashi, V. B. (2018)
A low-cost medium for the amylolytic lactic acid bacterium, Enterococcus faecium DMF78, was developed by response surface methodology using sago starch as substrate. Six nitrogen sources, wort, whey, corn steep liquor (CSL), trub, soybean and mungbean flour were evaluated to completely eliminate or dramatically reduce the use of expensive yeast extract, beef extract, and proteose peptone in the medium. Highest lactic acid yield was achieved using a medium with 35.0% whey, 25.0% wort, 3.0% diluted CSL and 0.076% proteose peptone in the standard formulation of de Mann, Rogosa and Sharpe (MRS) medium. Validation run of the optimized medium in the 2-L fermentor revealed slightly lower starch utilization (0.75 g/g) and low cell growth, but high lactic acid yield of 28.83 g/L after 24 hours, as compared to fermentation using complete sago-MRS medium.